The Architectural Decodification of Twin Towers: An Investigation into Cultural Communication and Related Symbolism Unrecognized by the Surrounding Community: The Architectural Decodification of Twin Towers: An Investigation into Cultural Communication and Related Symbolism Unrecognized by the Surrounding Community - An-Najwa, Rahilla; Fa'adihilah Tahnia, Talita (JOSAR (Journal of Students Academic Research), 2024)
The people of UIN Sunan Ampel Surabaya often hear the word "Twin Towers". In English, Twin Towers means towering towers or places. Most of the UIN Sunan Ampel community argues that, "in essence, the twin tower symbol symbolizes UINSA students are expected not to master religious knowledge only but if possible other sciences such as science etc." based on interviews conducted by researchers about understanding the value contained in the design and space of twin towers. This research is descriptive and qualitative. Twin Towers UIN Sunan Ampel Surabaya is the subject of research. Data was collected through interviews, documentation, and several book and journal references. Interviews were conducted to find out how students understand the value embodied in Twin Towers space and design and to gain a better understanding of Twin Towers space and design in a cultural context. As a result, we will know more about the motifs, symbols, and cultural values reflected in the architecture and interior decoration of buildings, as well as the use of architectural language that describes religious or regional identities. The results of this study show that researchers found a lot of philosophies that need to be practiced by the people of UIN Sunan Ampel Surabaya in addition to balancing between general science and religion. That is, it is expected that the entire community of UIN Sunan Ampel Surabaya will participate in promoting culture and religious values and culture because the Twin Towers Design combines elements of Indonesian culture, such as Javanese architectural motifs and modern elements.